Evaluating the gray and white matter energy budgets of human brain function. Issue 8 (August 2018) - Yu, Yuguo; Herman, Peter; Rothman, Douglas L; Agarwal, Divyansh; Hyder, Fahmeed
The insatiable appetite for energy to support human brain function is mainly supplied by glucose oxidation (CMRglc(ox) ). But how much energy is consumed for signaling and nonsignaling processes in gray/white matter is highly debated. We examined this issue by combining metabolic measurements of gray/white matter and a theoretical calculation of bottom-up energy budget using biophysical properties of neuronal/glial cells in conjunction with species-exclusive electrophysiological and morphological data. We calculated a CMRglc(ox) -derived budget and confirmed it with experimental results measured by PET, autoradiography, 13 C-MRS, and electrophysiology. Several conserved principles were observed regarding the energy costs for brain's signaling and nonsignaling components in both human and rat. The awake resting cortical signaling processes and mass-dependent nonsignaling processes, respectively, demand ∼70% and ∼30% of CMRglc(ox) . Inhibitory neurons and glia need 15–20% of CMRglc(ox), with the rest demanded by excitatory neurons. Nonsignaling demands dominate in white matter, in near opposite contrast to gray matter demands. Comparison between 13 C-MRS data and calculations suggests ∼1.2 Hz glutamatergic signaling rate in the awake human cortex, which is ∼4 times lower than signaling in the rat cortex. Top-down validated bottom-up budgets could allow computation of anatomy-based CMRglc(ox) maps and accurate cellular level interpretation of brain metabolic imaging.